Immunoglobulin Rapid Test Sensitivity in PCR-Positive COVID-19 Patients - Ahmad A. Alharbi; Mohammad K. Alshomrani; Abdullah A. Alharbi; Abdulrahman H. Almaeen; Saad AlAsiri; Awad Al-Omari; Imad Alishat; Saeed Dolgom (Dr. Sulaiman Al Habib Medical Journal)
Background Diagnostic assays aimed at the identification of immunoglobulin G (IgG) and immunoglobulin M (IgM) offer a rapid and adjunct modality to conventional real-time reverse transcription polymerase chain reaction (rRT-PCR) assays for the diagnosis of coronavirus disease 2019 (COVID-19). Aim To analyze the sensitivity of IgG and IgM-based serological assays in rRT-PCR-positive COVID-19 subjects. Methods A consecutive cohort of 69 patients with COVID-19-related symptoms or recent exposure to COVID-19-positive individuals were included after taking informed consent. Nasopharyngeal swabs for SARS-CoV-2 rRT-PCR analysis and venous blood samples for the COVID-19 IgG/IgM rapid test were simultaneously collected from each subject on day 0. Then, in the case of positive PCR results, subsequent blood samples for COVID-19 IgG/IgM analysis were collected on days 7, 10 and 14. Samples were statistically analyzed to determine the sensitivity of the serology-based assays. Results No correlation was found between age or sex and the rRT-PCR, IgG and IgM results; 65.2% of subjects tested positive by rRT-PCR. The sensitivity of the IgM and IgG rapid test increased gradually with time, reaching the highest level on day 14 (22.2% and 72%, respectively). Conclusion Serological assays for the detection of infection with SARS-CoV-2 were compared to rRT-PCR. These assays yielded lower sensitivities than rRT-PCR-based assays. However, given that these immunoassays are more affordable, faster, and easier to execute, they could be recommended for epidemiological research or characterizing the immune status of postinfection or post-vaccination subjects.